Rekonstruksi Penafsiran Kesederhanaan Dan Implikasinya Terhadap Kemiskinan Struktural - Intan Nur Amalia; Ojim; Haris Muslim; Mimin Muhaemin (Jurnal Syntax Fusion, 2026)
This study examines the high rate of poverty in Indonesia, particularly among Muslims, which is often associated with a misconceived understanding of simplicity in Islamic teachings. Simplicity is frequently interpreted as passive acceptance of deprivation and even regarded as a sign of piety, reinforcing structural poverty and social injustice. This research aims to deconstruct and reconstruct the Qur’anic concept of simplicity by emphasizing a liberative interpretation that promotes social justice rather than resignation. The study employs a qualitative approach through discourse analysis and thematic interpretation. It focuses on Qur’anic verses related to poverty and simplicity, while analyzing the social discourse shaped by their interpretations. This research is a library study, drawing on primary sources such as the Qur’an and classical as well as contemporary tafsir works, alongside relevant scholarly references. The theoretical framework combines Al-Farmawi’s thematic tafsir method and Anthony Giddens’ structuration theory to explain how individuals can critically engage with and transform oppressive social structures through reflexive action. The findings from QS. Al-Furqan: 67, QS. Al-A’raf: 29, and QS. An-Nisa: 79 indicate that simplicity in Islam is closely related to justice, self-restraint, and social responsibility in controlling consumerism. These results demonstrate that Islam does not legitimize poverty but calls for justice and resistance against oppressive structures.